Eksplorasi terhadap Paradigma Penyebaran Islam Para Rasul ‘Ulul Azmi: Analisis dari Perspektif Sejarah Islam : Exploring the Paradigms of Islamic Propagation of ‘Ulul Azmi Prophets: An Analysis from Islamic Historical Perspectives - Anshory, Anhar; Awang, Ramli; Haron, Zulkiflee; Ramli, Ahmad Faizuddin (Journal of Al-Tamaddun, 2023)
The concept of revelation is commonly associated with reveal prophets, who serve as conduits for delivering God’s messages to mankind. This article explores the methodology employed by five prominent prophets of Ulul ‘Azmi – prophet Noah a.s., prophet Abraham a.s, prophet Moses a.s., prophet Jesus a.s. and prophet Mohammad s.a.w., in propagating Islam – with a particular focus on their method to delivering the Islamic monotheism (tawhid) message. The objective of this study is to identify and analyze the methodologies utilized by these prophets in their mission to propagate Islam. The research methodology employed is qualitative in nature, utilizing content analysis techniques. Primary sources, such as the Quran and Hadith, along with the works of Islamic scholars, are referenced to gain insights into the methodologies adopted by the prophets. The findings of this study reveal three key methods employed by the prophets, namely, oral, action, and writing. These approaches are thoroughly examined and analyzed within the context of their respective prophets and their specific circumstances. Ultimately, the article concludes by providing an overview of the identified methodologies and their significance in the propagation of Islam, shedding light on the diverse approaches and strategies utilized by the prophets to convey the message of Islamic monotheism.